The impact of employee benefits towards organizational commitment in SMIs Kedah / Prof. Madya Dr. Zaliha Hj. Hussin…[et al.] - Hj Hussin, PM Dr. Zaliha; Ju, Soon Yew; Ladisma @ Awis, Mahadir; Zainuddin, Azizan (Research Management Institude, 2005)
The purpose of this study is to examine from the employees’ point of view, what are the employee benefits i.e. mandatory and voluntary benefits provided by their employers and the employees’ organizational commitment. The data of this study were collected from 256 employees in food manufacturing industries, SMIs, Kedah from mid July - mid September 2004. There are four research objectives concerning this study: (i) to identify the types of mandatory and voluntary benefits given by the employer of SMIs, Kedah; (ii) to investigate the level of organizational commitment among the employees of SMI’s Kedah; (iii) to identify the relationship between employee benefits (mandatory and voluntary benefits) and organizational commitment; and (iv) to identify the demography background (gender, age, marital status and years of service) and organizational commitment. The first research objective is to identify the types of mandatory and voluntary benefits given by the employer of SMI’s Kedah. Result of this study indicated that majority of the employers complied with legal requirement by providing mandatory benefits to their employees. However, a small number of respondents indicated that their employees did not provide them mandatory benefits. Result also shows that among voluntary benefits, bonus and uniform are the most frequent mentioned voluntary benefits given by employers. Second research objective is to investigate the level of organizational commitment among the employees of SMI’s Kedah. Result shows that the employees of food manufacturing industries in SMIs, Kedah having high organizational commitment. Third research objective is to identify the relationship between employee benefits (mandatory and voluntary benefits) and organizational commitment. Finding indicated that employee benefits (mandatory and voluntary benefits) were having significant and positive relationship with organizational commitment and voluntary benefits having higher relationship as compare to mandatory benefits. This finding suggested that when employees received more employee benefits (mandatory and voluntary benefits) their organization commitment tend to be higher. Lastly, fourth research objective is to identify the demography variables (gender, age, marital status and years of service) and organizational commitment. Results suggested that among the demographic variables, gender, age and marital status are having significant association with organizational commitment